Matrix-induced fragmentation of P3′-N5′ phosphoramidate-containing DNA: high-throughput MALDI-TOF analysis of genomic sequence polymorphisms - Shchepinov, Mikhail S. (Oxford University Press, 2001)
Chemical and enzymatic approaches were used to produce polynucleotide fragments containing acid-labile internucleotide P3′-N5′ phosphoramidate bonds, either in a surface-bound form or in solution. The primer extension reaction utilizing 5′-amino-5′-deoxynucleoside 5′-triphosphates generates polynucleotides that can be fragmented into short, easy-to-analyze pieces simply by being premixed with the acidic matrices typically used for MALDI-TOF mass spectrometry of nucleic acids. This leads to detection procedures that are simple, robust and easy to automate. Utilizing this approach, a polymorphic site in the human ADRB3 gene was interrogated. Primer extensions with phosphoramidate analogs of dNTPs allowed for unambiguous discrimination of all possible genotypes.